2015
DOI: 10.1111/1467-8268.12145
|View full text |Cite
|
Sign up to set email alerts
|

How Relevant Is the Capital Asset Pricing Model (CAPM) for Tests of Market Efficiency on the Nigerian Stock Exchange?

Abstract: We find an asset pricing model which consists of the market portfolio, the market skewness or co‐skewness factors, and portfolio idiosyncratic volatility factor best explains portfolio risk‐return trade‐offs on the Nigerian Stock Exchange (NSE), indicating this model is appropriate for studies of semi‐strong form efficiency of the Nigerian Stock Market. Our finding that an asset pricing model which consists of the market portfolio alone tends to consistently understate portfolio risk indicates this conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The results of hypotheses testing revealed the single-factor capital asset pricing model is invalid in the Jordanian stock market. This conclusion is in line with the results of studies of many researchers who reached the same conclusion about this market (Alqisie & Alqurran, 2016;Alrgaibat, 2015;Blitz et al, 2013) and about many other countries (Dajčman et al, 2013;Dzaja, & Aljinovic, 2013;Li, Gan, Zhuo, & Mizrach, 2014;Nyangara et al, 2016;Obrimah et al, 2015;Saji, 2014;Wu et al, 2017). The hypothesized relationship between the expected rate of return and variables of size, financial leverage, and market rate of return was found to be insignificant ; the expected rate of return for a stock is directly related to the operating leverage of the stock.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of hypotheses testing revealed the single-factor capital asset pricing model is invalid in the Jordanian stock market. This conclusion is in line with the results of studies of many researchers who reached the same conclusion about this market (Alqisie & Alqurran, 2016;Alrgaibat, 2015;Blitz et al, 2013) and about many other countries (Dajčman et al, 2013;Dzaja, & Aljinovic, 2013;Li, Gan, Zhuo, & Mizrach, 2014;Nyangara et al, 2016;Obrimah et al, 2015;Saji, 2014;Wu et al, 2017). The hypothesized relationship between the expected rate of return and variables of size, financial leverage, and market rate of return was found to be insignificant ; the expected rate of return for a stock is directly related to the operating leverage of the stock.…”
Section: Discussionsupporting
confidence: 85%
“…The validity of this model was tested by many researchers in many countries (Chaudhary, 2017;El-Mousallamy & El-Masry, 2016;Nyangara, Nyangara, Ndlovu, & Tyavambiza, 2016;Obrimah, Alabi, & Ugo-Harry, 2015;Saji, 2014;Sattar, 2017;Wu et al, 2017). Some researchers supported the validity of the model (Bajpai & Sharma, 2015;Bjuggren & Eklund, 2015;Lee, Cheng, & Chong, 2016;Novak, 2015) while others concluded that the model is invalid in estimating the expected rate of return on the financial asset (Alqisie & Alqurran, 2016;Alrgaibat, 2015;Chaudhary, 2017;Wu et al, 2017).…”
Section: Capital Asset Pricing Modelmentioning
confidence: 99%
“…At the individual level, Bodie et al (2014) denote that the following areas are essential for measuring a firm's performance: (1) Level of leverage, (2) Efficiency in the use of assets, (3) Liquidity management, and (4) Return on investment. On the other hand, at the collective level, Obrimah et al (2015) propose that the market is influenced by microeconomic variables that specifically affect the productive sector in question, as well as macroeconomic variables that alter asset prices throughout the economy. These can be political-legal, technological, social, environmental, or economic per se.…”
Section: Return Of Sharesmentioning
confidence: 99%
“…As reported by Kumar and Goyal (2015), the majority of studies concerning the behavioral biases among investors were conducted in the United States and other developed countries with a few studies conducted in the developing countries. Behavioral finance is important in emerging markets because the traditional asset pricing models are invalid in some of these markets including the capital asset pricing model (Alqisie & Alqurran, 2016;Chaudhary, 2017;Elshqirat & Sharifazdeh, 2018;Obrimah, Alabi & Ugo-Harry, 2015;Soumaré , Amé nounvé , Diop, Mé ité & N'sougan, 2013) and the arbitrage pricing theory (Elshqirat, 2019;Gul & Khan, 2013;Okoro, 2017). Concerning herding behavior, however, the same conclusion about the lack of studies in emerging markets can be noted (Kumar & Goyal, 2015).…”
Section: Herding Behaviormentioning
confidence: 99%